Blunt splenic injury, Emergency Department to discharge: A Western Trauma Association critical decisions algorithm. Issue 3 (18th March 2023) - Shatz, David V.; de Moya, Marc; Brasel, Karen J.; Brown, Carlos V.R.; Hartwell, Jennifer L.; Inaba, Kenji; Ley, Eric J.; Moore, Ernest E.; Peck, Kimberly A.; Rizzo, Anne G.; Rosen, Nelson G.; Sperry, Jason L.; et al.
Abstract : This document outlines both management of these patients in the emergency and operating rooms, and provides guidance for the subsequent days and weeks following injury for those undergoing nonoperative treatment (observation or splenic angioembolization). Abstract :